(untitled) (Communication & Society, 2016)
This article examines the different ways of interaction that young people have with television and online video content. Inspired by Van Dijck’s argument (2009), that there is a misleading assumption to define the audience in terms of passive recipients related to old media (e.g. television) and active participants who are internet users, the aim of this study is, firstly, to analyze if there are differences related to the type of medium; and, secondly, to examine if it is possible to develop an audience interaction typology in relation to television and to video content. The study presents the most significant statistical results of a survey of 475 students conducted at Mondragon University. After carrying out a factorial analysis, two multiple generalized linear regressions and a cluster analysis, our results show that it is statistically impossible to describe the audience’s attitude as a dichotomy between passive television viewers and active internet users. Likewise, it is not possible to develop an audience interaction typology in relation to television and to video content. The results rather show a multifarious profile of activity patterns related to specific contents and interactive practices on the Web. This study illustrates the complexity of content, context and audience practices in the new media environment.